Construction of a genetic map and QTL mapping of seed size traits in soybean - Jiang, Aohua; Liu, Jiaqi; Gao, Weiran; Ma, Ronghan; Tan, Pingting; Liu, Fang; Zhang, Jian (Frontiers in Genetics, 2023)
Soybean seed size and seed shape traits are closely related to yield and appearance quality. In this study, 186 individual plants of F2 generation derived from crosses between Changjiang Chun 2 and Jiyu 166 were selected as the mapping population to construct a molecular genetic linkage map, and the phenotypic data of hundred grain weight, seed length, seed width and seed length-to-width ratio of soybean under three generations of F2 single plants, F2:3 and F2:4 lines were combined to detect QTL for the corresponding traits by ICIM mapping. A soybean genetic map containing 455 markers with an average distance of 6.15 cM and a total length of 2799.2 cM was obtained. Fiftyeight QTL related to hundred grain weight, seed length, seed width and length-to-width ratio of soybean were obtained under three environmental conditions. a total of 10 QTL were detected in more than two environments with a phenotypic variation over 10%. Twelve QTL clusters were identified on chromosomes 1, 2, 5, 6, 8, 13, 18, and 19, with the majority of the overlapping intervals for hundred grain weight and seed width. These results will lay the theoretical and technical foundation for molecularly assisted breeding in soybean seed weight and seed shape. Eighteen candidate genes that may be involved in the regulation of soybean seed size were screened by gene functional annotation and GO enrichment analysis.